TRADISI RIHLAH âILMIYYAH DI KALANGAN ULAMA HADIS - Nirwana, Dzikri (Faculty of Ushuluddin and Humanities, 2015)
The tradition of hijrah seek knowledge often referred to as the âilmiyyah rihlah travel or study that has beenÂ inherited by those earlier (the salaf al-shÃ¢lih) to the current generation. This paper specifically highlights theÂ rihlah âilmiyyah tradition among the scholars of Hadith in historical perspective. The presence technologicalÂ advances and information now that itâs been more advanced, as well as easily accessible online anytime and anyÂ where, does not mean rihlah â ilmiyyah by the time this becomes less relevant again. However, because a meetingÂ directly with the teachers remain necessary in order to keep the scientific ethics and objectivity of scholarshipÂ which in turn will generate sustainable goodness value, or in the language of religion is referred to as the âblessing â of science. This was the movitasi scholars of classical tradition to keep doing this to perlawatanÂ seeking other areas, despite having to go through the difficulties and obstacles.